1984
DOI: 10.1080/19485565.1984.9988558
|View full text |Cite
|
Sign up to set email alerts
|

The costs and benefits of screening for PKU in Wisconsin

Abstract: A comprehensive benefit-cost analysis of the screening program to detect newborns with PKU in Wisconsin is presented. Classic PKU is a genetic disorder which, if undetected and untreated during the first few weeks of life, generally results in mental retardation and a variety of other abnormal conditions. Monetary costs of the detection and treatment program were compared with the projected benefits (avoided costs) that result from the prevention of the mental retardation associated with the disorder. Future c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
18
1
1
Order By: Relevance
“…Our results indicate that instituting universal newborn screening for MCADD can be achieved at an incremental cost of $5600 per QALY saved, or $11 000 per life-year saved, over a 20-year horizon and is therefore a highly cost-effective intervention. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The case for screening is further strengthened when the incremental ratio over a 70-year horizon is considered, as the respective ratios are $100 and $300. Probabilistic sensitivity analysis yielded 95% CIs for the estimated incremental cost-effectiveness ratios, with upper limits that equaled $17 100/ QALY ($33 800/life-year) for the 20-year horizon and $6900/QALY ($13 000/life-year) for the 70-year ho- rizon.…”
Section: Model Predictionsmentioning
confidence: 99%
“…Our results indicate that instituting universal newborn screening for MCADD can be achieved at an incremental cost of $5600 per QALY saved, or $11 000 per life-year saved, over a 20-year horizon and is therefore a highly cost-effective intervention. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The case for screening is further strengthened when the incremental ratio over a 70-year horizon is considered, as the respective ratios are $100 and $300. Probabilistic sensitivity analysis yielded 95% CIs for the estimated incremental cost-effectiveness ratios, with upper limits that equaled $17 100/ QALY ($33 800/life-year) for the 20-year horizon and $6900/QALY ($13 000/life-year) for the 70-year ho- rizon.…”
Section: Model Predictionsmentioning
confidence: 99%
“…Otros países han mostrados incluso ratios más altos. Los mayores beneficios son los de evitar las cargas que para la sociedad y la familia suponen los costos de los niños con retraso mental (25,26).…”
Section: Discussionunclassified
“…Twelve published economic evaluation studies were identified (Table 25). 132,[157][158][159][160][161][162][163][164][165][166][167] Ten of these [157][158][159][160][161][162][163][164][165][166] were CBAs, with quantification of monetary costs and benefits. Two were simpler cost-effectiveness analyses (CEAs) 132,167 which calculated only the cost of screening per case detected.…”
Section: Number and Type Of Economic Evaluation Papers Identifiedmentioning
confidence: 99%
“…In all there were eight studies [157][158][159][160][161]163,164,166 in which the costs and benefits of neonatal screening for PKU were estimated (see Table 26). These covered very different populations and the number of cases detected varied considerably, from 1.2 to 17.9 per 100,000 babies screened.…”
Section: The Economics Of Pku Screeningmentioning
confidence: 99%
See 1 more Smart Citation